STRATEGI PEMBERDAYAAN SISWA DALAM UPAYA MENCIPTAKAN SEKOLAH SEHAT - Ade Tutty Rokhayati Rosa; Endi Jamjuri; Iwan Setiawan; Lindawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the management of student empowerment strategies in creating a healthy school environment at SD Negeri Sukajaya, Cianjur Regency, and SD Negeri Legokbedo, Bandung Regency. The research problem arises from the fact that the implementation of school health programs, particularly Clean and Healthy Living Behavior (Perilaku Hidup Bersih dan Sehat/PHBS), has not been optimally managed, even though daily hygiene and health practices are routinely carried out in schools. This study employed a qualitative approach with a case study design. Data were collected through in-depth interviews, observations, and documentation studies involving principals, teachers, and related stakeholders. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that student empowerment strategies are implemented through habitual clean and healthy behaviors, active student involvement in school hygiene activities, and teachers’ role modeling. These practices contribute positively to the development of a clean and healthy school culture. However, the management of these strategies has not been fully supported by formal planning documents, well-documented organizational structures, or measurable supervision and evaluation instruments. As a result, the implementation of student empowerment strategies tends to be functional but remains informal and highly dependent on individual initiatives. From a management perspective, the findings align with G. R. Terry’s grand theory of management, which emphasizes the integration of four key functions: planning, organizing, actuating, and controlling. The study reveals that the actuating function has been relatively well implemented, while the planning, organizing, and controlling functions require significant strengthening. Therefore, reinforcing managerial aspects—particularly systematic planning, clear organizational arrangements, and structured supervision—is essential to ensure that student empowerment strategies in promoting healthy schools can be implemented more systematically, consistently, and sustainably.